Concurrent functional magnetic resonance imaging and electroencephalography assessment of sensory gating in schizophrenia. Issue 8 (4th December 2013) - Bak, Nikolaj; Rostrup, Egill; Larsson, Henrik B.W.; Glenthøj, Birte Y.; Oranje, Bob
Abstract Schizophrenia is frequently accompanied by deficits in basic information processing, such as sensory gating. The sources behind deficient sensory gating in schizophrenia patients are, however, still largely unclear. The aim of the current study was to identify the brain structures involved in deficient sensory gating in schizophrenia patients. Twenty healthy male volunteers and 23 male schizophrenia patients were initially assessed in a somatosensory P50 suppression paradigm using concurrent electroencephalography (EEG)/functional magnetic resonance imaging (fMRI) methodology. The trials consisted of single stimuli or pairs of identical stimuli with either 500 ms or 1, 000 ms interstimulus intervals. Not all subjects showed a P50 waveform as a result of the somatosensory stimuli: It was detected in 13 schizophrenia patients and 15 control subjects. Significant P50 suppression was found in the 500 ms trials in controls only. Region of interest analyses were performed for a priori chosen regions. Significant negative correlations between P50 ratios and the BOLD response were found bilaterally in the hippocampus, thalamus, anterior and posterior superior temporal gyrus (STG), and in the left inferior frontal gyrus pars opercularis. However, significant group differences were found in the hippocampus and the thalamus only. This is the first study in which P50 suppression was assessed in schizophrenia patients with concurrent fMRI/EEG methodology. The data support that the STG, thalamus, inferior frontal gyrus, and the hippocampus are involved in P50 suppression. However, of these structures only the hippocampus and thalamus appeared involved in the altered sensory processing found in schizophrenia. Hum Brain Mapp 35:3578–3587, 2014. © 2013 Wiley Periodicals, Inc.